2023
DOI: 10.1111/ijn.13142
|View full text |Cite
|
Sign up to set email alerts
|

Achieving nursing students' clinical practice hours during the COVID‐19 pandemic: Effects of alternative and nonstandard practicum methods

Abstract: Aim The aim of this study is to examine nursing students' experiences of alternative and nonstandard practicum methods used during the Coronavirus Disease 19 (COVID‐19) pandemic and the associations between these experiences and nursing students' anxiety with clinical decision‐making. Background Nursing students experiencing alternative clinical practice methods during the COVID19 pandemic have expressed regrets about being unable to experience direct nursing care and doubts about their clinical decision‐makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…This may be the reason for the relatively high proportion of on-site clinical practice in this study sample compared to other programs. Other studies showed that the proportion of on-site clinical practice was 57.52% in 2020, 34 and most students had less than 40% of on-site clinical practice in 2021. 35 The proportion of on-site clinical practice in this study was higher than in other studies because the university student participants had a tertiary general hospital as a partner hospital, which allowed easy access to on-site clinical practice.…”
Section: Discussionmentioning
confidence: 96%
“…This may be the reason for the relatively high proportion of on-site clinical practice in this study sample compared to other programs. Other studies showed that the proportion of on-site clinical practice was 57.52% in 2020, 34 and most students had less than 40% of on-site clinical practice in 2021. 35 The proportion of on-site clinical practice in this study was higher than in other studies because the university student participants had a tertiary general hospital as a partner hospital, which allowed easy access to on-site clinical practice.…”
Section: Discussionmentioning
confidence: 96%
“…Se reportaron mayormente las experiencias a la migración curricular de un esquema presencial tradicional a uno que involucraba la tecnología desde los espacios formativos teóricos hasta en escenarios prácticos. (10)(11)(12)(13) Se ha reportado que esto contribuyó a innovar en los procesos formativos y a favorecer el desarrollo de habilidades de trabajo en equipo, responsabilidad, escucha activa y autonomía en los estudiantes. (14) Dentro de los aspectos que más se ha referido que inciden en la percepción y satisfacción del estudiantado, la preparación del docente es uno de los más relevantes.…”
Section: Discussionunclassified
“…The COVID-19 pandemic necessitated widespread changes in nursing education worldwide, including in Japan, where universities were compelled to adapt nursing practicums to maintain educational quality and minimize disruptions for students [ 1 , 2 , 3 ]. In response to the pandemic’s challenges and the need for infection prevention measures, innovative programs integrating information technology, simulations, and online learning emerged.…”
Section: Introductionmentioning
confidence: 99%